Grid expansion factor for the shooting method solution of convection-diffusion equation - Abdullah, Aslam (Asian Research Publishing Network (ARPN), 2019)
The essential nature of convection-diffusion related problems is the main reason why they are found in various science and engineering applications. This includes the computational fluid dynamics problems of grid structure for the numerical calculations. In this research, the importance of the relationships between the grid structure and the flow parameters is emphasized. A systematic technique in setting the parameter of interest is applied. In particular, we present the a posteriori formulation of low Peclet number based grid expansion factor for the numerical solution of convectiondiffusion equation. The resulting function which is ‘many-to-one’ serves as a standard for a more efficient decision-making in the determination of the computational domain grid, and in eliminating some heuristic aspects of the scalar concentration prediction. The results confirm the effectiveness of the new approach.